Modelling the residual mean meridional circulation at different stages of sudden stratospheric warming events - Koval, Andrey V.; Chen, Wen; Didenko, Ksenia A.; Ermakova, Tatiana S.; Gavrilov, Nikolai M.; Pogoreltsev, Alexander I.; Toptunova, Olga N.; Wei, Ke; Yarusova, Anna N.; Zarubin, Anton S. (Annales Geophysicae, 2021)
Ensemble simulation of the atmospheric general circulation at altitudes up to the lower thermosphere is performed using the 3-D nonlinear mechanistic numerical model MUAM. The residual mean meridional circulation (RMC), which is the superposition of the mean Eulerian and wave-induced eddy components, is calculated for the boreal winter. Changes in the vertical and meridional RMC velocity components are analysed at different stages of a simulated composite sudden stratospheric warming (SSW) event averaged over 19 model runs. The simulation results show a general decrease in RMC velocity components up to 30 % during and after SSW in the mesosphere and lower thermosphere of the Northern Hemisphere. There are also increases in the downward and northward velocities at altitudes of 20–50 km at the northern polar latitudes during SSW. Associated vertical transport and adiabatic heating can contribute to warming the stratosphere and downward shifting of the stratopause during the composite SSW. The residual mean and eddy mass fluxes are calculated for different SSW stages. It is shown that before the SSW, planetary wave activity creates wave-induced eddy circulation cells in the northern upper stratosphere, which are directed upwards at middle latitudes, northward at high latitudes and downwards near the North Pole. These cells increase heat transport and adiabatic heating in the polar region. During SSW, the region of upward eddy vertical velocity is shifted to high latitudes, but the velocity is still downward near the North Pole. After SSW, upward eddy-induced fluxes span the entire polar region, producing upward transport and adiabatic cooling of the stratosphere and providing the return of the stratopause to higher altitudes. The obtained statistically significant results on the evolution of RMC and eddy circulation at different SSW stages at altitudes up to the lower thermosphere can be useful for a better understanding the mechanisms of planetary wave impacts on the mean flow and for the diagnostics of the transport of conservative tracers in the atmosphere.